Study about Massive MIMO Communication - Anuj Kumar Sharma; Vipul Sharma; Shiv Kumar Singh (Techniques and Innovation in Engineering Research Vol. 2, 2022)
To manage the expanding wireless data traffic, every new network generation needs to make a significant improvement in area data throughput. By enhancing spectral efficiency (bit/s/Hz/cell), Massive MIMO technology can increase area throughput by at least ten times while using the same base station density and bandwidth as existing networks. The base stations are outfitted with arrays of 100 antennas to enable the spatial multiplexing of tens of user terminals, which results in these astounding gains. Using Massive MIMO technology, numerous active users may be served by a base station that has a lot of antennas. System capacity would significantly rise because to MIMO Technology’s ability to concentrate sent signal energy in extremely small areas. Even while this novel idea has some exciting advantages, it also produces a fresh conflict that has attracted the interest of both academics and business. Impaired hardware and architecture, channel state information acquisition, channel feedback, immediate reciprocity, statistical reciprocity, and others [1]. This chapter describes the fundamental rationale and communication theory underlying the Massive MIMO technology.